Validação e Certificação digital de CV - Joana Lopes Beleza (2017)
More and more professionals are adopting the digital CV due to the visibility provided by online platforms. However, the information these CV hold may lack veracity and needs to be validated. Also, it is hard to measure the value of a certification. Valid and certified information is the most important issue for job recruiters. Dealing with a large number of proposals and resumes is time wasting and not very productive. Companies could increase focus on other important areas by decreasing the effort it takes to analyse resumes, since hiring managers struggle to tell which information can be trusted and which cannot. The solution is to implement a tool that digitally validates and certifies CV in a professional network of candidates and that is integrated with ApplyIT, a human resources management platform developed by Winprovit. The validation is done by assembling and analysing several official information sources and tools that can verify the contents of a CV: academic background, professional experience, certificates, research and skills. These sources can be Educational institution records; Professional institution records; Scholarly activity and Connections with other professionals. The vast information contained in Social Network Sites (SNS) can also be examined to obtain a better perspective of the candidate's profile and suitability for the job. The certification is done by contacting a well-known Certificate Authority that issues a digital certificate assigning a digital signature to the CV holder, proving the authenticity of the CV. A new digital certificate must be issued every time the candidate wants to modify or add information to the CV. By applying this digital validation and certification, the amount of CV with misleading information is cut down and the time it takes to find the best candidate for a specific position may be highly reduced. This also leads to more reliable and authentic information that draws the attention of hiring managers. Candidates should also be concerned with the reliability and confidentiality of their CV. The developed tool will be used in case studies to validate real CV of candidates registered in the ApplyIT platform, providing statistics regarding the percentage of information that can be verified in each CV.